A Review of the 'Urf Tradition of Mangompa Manuk in Mandailing Traditional Party: Case Study of Mandailing Community - Urrahman, M. Aulia; Madina, Dinda Difia; Kurniawan, M. Rafli (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
In this paper the author will examine the tradition of Mangompa Manuk (Carrying Chicken) in the traditional wedding party of Mandailing people that has existed for a long time. Mandailing people believe that this tradition must be carried out because this tradition is one of a series of stages in traditional Mandailing marriage. The purpose of this research is to find out the opinion of indigenous people about the Mangompa Manuk tradition and how the impact of the community who carry out the tradition. Furthermore, about the legal position in the Mangompa Manuk tradition, especially in 'urf analysis. This research uses a qualitative method. Data was collected by conducting interviews. In addition, data was obtained by looking at documents from books, theses, journals, and other scientific works. While the findings of the researchers that 4 out of 5 people who carry out the tradition are blessed with sustenance and good and smooth offspring. Meanwhile, based on the view of Islamic law, based on 'Urf analysis, the Mangompa Manuk tradition is categorized as 'Urf Shohih because the practice does not violate Shari'a on condition that when undergoing the tradition does not believe that offspring and wealth come from carrying out this custom, and can be categorized as 'Urf Fasid when it believes that carrying out this custom can provide offspring and wealth.